Prevalence of sleep-disordered breathing in an African general population: The Benin Society and Sleep (BeSAS) study - WACHINOU, ABLO PRUDENCE; HOUEHANOU, CORINNE; ADE, Serge; Agodokpessi, G. (My University, 2022)
Sleep apnea, Africa, adult